Music and Empathy - King, Elaine; Waddington, Caroline (Taylor & Francis, 2017)
In recent years, empathy has received considerable research attention as a means of understanding a range of psychological phenomena, and it is fast drawing attention within the fields of music psychology and music education. This volume seeks to promote and stimulate further research in music and empathy, with contributions from many of the leading scholars in the fields of music psychology, neuroscience, music philosophy and education. It exposes current developmental, cognitive, social and philosophical perspectives on research in music and empathy, and considers the notion in relation to our engagement with different types of music and media. Following a Prologue, the volume presents twelve chapters organised into two main areas of enquiry. The first section, entitled 'Empathy and Musical Engagement', explores empathy in music education and therapy settings, and provides social, cognitive and philosophical perspectives about empathy in relation to our interaction with music. The second section, entitled 'Empathy in Performing Together', provides insights into the role of empathy across non-Western, classical, jazz and popular performance domains. This book will be of interest to music educators, musicologists, performers and practitioners, as well as scholars from other disciplines with an interest in empathy research.